Entrepreneurship, Regional Development and Culture 2015
DOI: 10.1007/978-3-319-15111-3_5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cultural Factors on Social Entrepreneurship: The Impact of the Economic Downturn in Spain

Abstract: The purpose of this chapter is to analyze the influence of cultural factors on social entrepreneurship in Spain in the context of the recent economic crisis. Data from Global Entrepreneurship Monitor (GEM) and Spanish Statistics Institute (INE) for the period 2005-2010 are used as the main sources of information and a panel data analysis is applied in the empirical part of the research. Through the lens of institutional economics, the main findings of the study suggest that informal factors such as cultural fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
3
2
0
Order By: Relevance
“…The results of our research indicate a positive and statistically significant relationship. This result is in line with the results of previous studies [70], indicating a statistically significant and positive relationship between the observed variables, especially in the years marked as the period of economic crisis. This can be explained by the fact of more pronounced social problems in times of crisis and the emphasis on the importance of entrepreneurship and entrepreneurs as carriers of economic change and recovery.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of our research indicate a positive and statistically significant relationship. This result is in line with the results of previous studies [70], indicating a statistically significant and positive relationship between the observed variables, especially in the years marked as the period of economic crisis. This can be explained by the fact of more pronounced social problems in times of crisis and the emphasis on the importance of entrepreneurship and entrepreneurs as carriers of economic change and recovery.…”
Section: Discussionsupporting
confidence: 93%
“…This can be explained by the fact of more pronounced social problems in times of crisis and the emphasis on the importance of entrepreneurship and entrepreneurs as carriers of economic change and recovery. When it comes to media impact, we expected a positive relationship; however, the results were contrary to expectations but consistent with some studies [22,70] that conducted their research in Spain on two different geographical areas, different cultural and historical heritage, and different development paths, within which the same results appear. One possible explanation may be the greater impact of social media on social enterprises [72,73], which was omitted by the methodology used in this case.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Leković et al [43] observed a positive relationship between entrepreneurship solving social problems and entrepreneurial intention, resonating with SDG 11 (Sustainable Cities and Communities), but a negative association with media coverage of new business success. Ferri et al [44] noted that the social image of entrepreneurship positively correlates with social entrepreneurship in times of financial crisis, supporting SDG 1 (No Poverty).…”
Section: Social Values Towards Entrepreneurship and Entrepreneurial I...mentioning
confidence: 94%
“…The Organization for Economic Cooperation and Development (OECD, 2014), the World Bank (WB, 2017), the United Nations Organization for Education, Science and Culture (UNESCO, 2014) and the World Health Organization (WHO, 2017) have recognized social entrepreneurship as fundamental for the sustainable development of populations, since it not only generates jobs, but also addresses challenges in an innovative way and encourages the construction of fair, inclusive and democratic societies with privilege to the care of the environmental. In addition, social entrepreneurship has a relationship with social structure (Seelos et al, 2011), innovation (Mulloth, Kickul & Gundry, 2016), identity capital (Lewis, 2016), creativity (Chell, Nicolopoulou & Karatas-Özkan, 2010), social capital (Mair & Martí, 2006;Westlund & Gawell, 2012), social integration (Friedman & Desivilya, 2010), geography (Smith & Stevens, 2010), sustainable development (Seelos , Ganly & Mair, 2006), politics and values (Cho, 2006;Garrigós-Simón, González-Cruz & Contreras-Pacheco, 2016), social innovation (Sabato, Vanhercke & Verschraegen, 2017), marginalization, inequality and poverty (Mongelli & Rullani, 2017), ethics (Dey & Steyaert, 2014) and culture (Ferri, Noguera & Urbano, 2015).…”
Section: Introductionmentioning
confidence: 99%